Identifying developmental adaptations to early‐life stress. Issue 1 (19th December 2021) - Szepsenwol, Ohad
Abstract: The adaptation‐based approach to development under stress emphasizes how early‐life environments calibrate the development of traits and capabilities in ways that increase evolutionary fitness. Rooted in evolutionary theory, the adaptation‐based approach offers an alternative to the prevailing deficit model for development under stress. The utility and impact of this approach, however, depend on the ability to find convincing evidence for developmental adaptations to stress and eliminate alternative explanations. In this essay, I briefly discuss some of the challenges faced by the adaptation‐based approach, specifically as it employs life history theory. I also suggest several avenues for improvement, including generating specific theoretical predictions, using consistent operational definitions, designing studies with adequate controls and assessing mediating pathways.